New species of the genus Amphichroum Kraatz, 1857 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China - Shavrin, Alexey V.; Smetana, Aleš (Zootaxa, 2018)
Eleven new species of the genus Amphichroum Kraatz, 1857 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) from China are described and illustrated: A. angustilobatum Shavrin & Smetana, sp.n. (Yunnan: Meili Xue Shan), A. assingi Shavrin & Smetana, sp.n. (Yunnan: Hengduan Mountains), A. longilobatum Shavrin & Smetana, sp.n. (Sichuan: Erlang Shan), A. maculosum Shavrin & Smetana, sp.n. (Yunnan: Diancang Shan), A. propinquum Shavrin & Smetana, sp.n. (Sichuan: Gongga Shan), A. schuelkei Shavrin & Smetana, sp.n. (Yunnan: Gaoligong Shan), A. rotundatum Shavrin & Smetana, sp.n. and A. squamosum Shavrin & Smetana, sp.n. (Sichuan: Daxue Shan, Gongga Shan), A. subaequale Shavrin & Smetana, sp.n. (Shaanxi: Qing Ling Shan), A. subelongatum Shavrin & Smetana, sp.n. (Sichuan: Erlang Shan, Daxue Shan), and A.tibetanum Shavrin & Smetana, sp.n. (Tibet: Chola Mountains). A key to species known from China and distributional maps of all species are provided.